THE CONCEPT OF INTERFERENCE AND ITS TYPES IN THE WORLD OF LINGUISTICS - Yormatova Yokuthon Nurmatovna (Scholar Express Journal, 2021)
The use of a foreign language is even more clearly manifested in intercultural communication as a result of the interaction of different cultures. This lays the foundation for the formation of sociocultural competence along with linguistic competence. The article discusses the issues of interconnection of language competence and interconnection of language contacts, interference as well as their reflection in the communicative process
Keywords: Bilingual and bilingualism; multilingualism; interference; types of interference